SMART PARENTING: TEACHING ENGLISH FOR KIDS AT HOME - Nanik Shobikah (PSGA LP2M IAIN Pontianak, 2019)
This article discusses the role of parents especially the mother in caring and guiding their children to learn and study English at home. English as a second language acquisition in Indonesia made this language important to be learned by children. The earlier the children study English, the better English they have. This study is a qualitative research using literature review method. The collection data used is literature review. The data are taken from the references deal with the research focus such as journals, articles, and books. This articles found that many activities can be occured by the smart parents in learning English at home with their children such as reading an English book stories, watching English movies, singing an English children song, coloring English vocabulary pictures, playing English vocabulary games, and playing a role play. The parents are also must prepare the English book stories, English children movies, English children songs, coloring English vocabulary pictures, and English vocabulary dictionary.